The Determinants of Purchase Intention towards Counterfeit Mobile Phones in Pakistan - Rizwan, Muhammad; Jamal, Muhammad Nasir; Zain-Ul-Abidin,; Zareen, Khadeeja Gul; Khan, Arslan; Farhat, Barza; Khan, Rashid (Asian Journal of Empirical Research, 2013)
The alarming emergence of global economic phenomenon of counterfeiting and the deficiency of research work in the context of consumer purchase intentions towards counterfeits makes the study more worthwhile than ever before. This study intends to examine the relationship of value consciousness, low price, past experience peer pressure and attitude on consumer purchase intentions in the context of counterfeit mobile phones in Pakistan. A sample of 329 students with the help of a questionnaire containing 22 statements related beliefs about counterfeited mobiles was taken. The data were analyzed using linear regression. The findings support the significant influence of past experience and low price on attitude towards counterfeit mobile phones, weak support for the role of value consciousness. Positive association between past experience, peer pressure and attitude towards counterfeit mobile phones were found and there is also a positive association of attitude with young consumer’s purchase intentions. Strangely, low price was not significant in influencing the purchase intentions. For both practitioners and academics, the findings of this study hold important implications. The paper guides the policy makers and academics about the main predictors of consumer’s attitude towards counterfeit mobile phones.